Synergistic Effect of Huangqin Decoction Combined Treatment With Radix Actinidiae chinensis on DSS and AOM-Induced Colorectal Cancer - Huang, Jianbo; Jiang, Tao; Kang, Jingyi; Xu, Jiayi; Dengzhang, Yiting; Zhao, Zhengqi; Yang, Chuqi; Wu, Mengting; Xu, Xiaoping; Zhang, Guangji; Lou, Zhaohuan (Frontiers in Pharmacology, 2022)
Objective: To demonstrate the effectiveness of Huangqin decoction (Huangqin Tang in Chinese, HQT) combined with Radix Actinidiae chinensis (Tengligen in Chinese, TLG) under the guidance of “dampness–heat theory” in preventing and treating colorectal cancer (CRC) with dampness–heat accumulation and to preliminarily reveal its mechanism. Methods: The mice model of CRC was established by intraperitoneal injection of AOM combined with consumption of 2.5% DSS solution, and celecoxib, HQT, TLG, and their combination (HQT + TLG) were administered at the same time. The physical signs and death of the mice were observed daily. At the end of the experiment, the colorectal tissue was dissected, and the tumor was observed and counted. HE staining and Masson’s staining were used to observe the histopathological changes of colon. Expression levels of TNF-α, IL-6, and IL-10 in colorectal tissue were detected by ELISA, and the expression of TNF-α was observed by immunofluorescence. TUNEL assay was used to observe the apoptosis of tumor tissues, and immunohistochemistry was used to observe the expression of Ki-67 and occludin. The mRNA expression levels of claudin-1, occludin, ZO-1, and IL-6 and IL-17 were detected by RT-PCR, and occludin, ZO-1, NF-κB, and STAT3 protein levels were detected by Western blot. The composition of intestinal flora was analyzed by 16S rRNA. Results: HQT + TLG could significantly reduce the mortality of model mice and improve the intestinal mucosal inflammatory cell infiltration and high-grade intraepithelial neoplasia in model mice. All administration groups show a great reduction in the levels of IL-6 and TNF-α in the colorectal tissues of model mice, and increase in the level of IL-10, the total number of CD3+ T cells, the proportion of CD3+CD4+ T cells, and the ratio of CD4/CD8. HQT and HQT + TLG could significantly change the composition of intestinal flora and increase the abundance of Firmicutes and Patescibacteria. Conclusion: HQT and TLG combination has a good effect on inhibiting AOM-DSS-induced CRC. This function may be related to improving the composition of the intestinal flora, regulating the proportion of T-cell subsets in colorectal lymphoid tissue to improve inflammatory response, and downregulating the expression of claudin-1, inhibiting the activation of IL-6/STAT3 signaling pathway to improving abnormal hyperplasia.